Governance Reform Under Real-World Conditions : Citizens, Stakeholders, and Voice - Odugbemi, Sina; Jacobson, Thomas (Washington, DC : World Bank, 2012)
This book is a contribution to efforts to improve governance systems around the world, particularly in developing countries. It offers a range of innovative approaches and techniques for dealing with the most important nontechnical challenges that prevent many of those efforts from being successful or sustainable. By so doing, the book sets out the groundwork for governance reform initiatives. Its overarching argument is that the development community is not lacking the tools needed for technical solutions to governance challenges. The toolbox is overflowing; best practice manuals in various areas of interest tumble out of seminars and workshops. However, difficulties arise when attempts are made to apply what are often excellent technical solutions under real-world conditions. Human beings, acting either alone or in groups small and large, are not as amenable as are pure numbers. And they cannot be put aside. In other words, in the real world, reforms will not succeed, and they will certainly not be sustained, without the correct alignment of citizens, stakeholders, and voice.